PENDIDIKAN KARAKTER DALAM BUKU INILAH JALAN KEPADA ALLAH KARYA SYEIKH MUHAMMAD SAID BONJOL - Hakekat Rabbani Ikhsan; Iswantir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the understanding that character education is not a new concept within the Islamic education system. In essence, the core of Islamic education is moral development, which is now commonly referred to as character education. This development is the responsibility of every Muslim individual, beginning with oneself, then extending to the family, and ultimately to society. However, since not all individuals are able to carry out this responsibility effectively, it is also undertaken by teachers (ustaz) and preachers (da’i) through both formal and non-formal educational institutions. In the Naqshbandi order, there is a method known as suluk or khalwat, which involves secluding oneself under the guidance of a mursyid (spiritual teacher). The true essence of suluk is not to attain worldly pleasures or divine favors, but solely to seek the pleasure of Allah. Despite ongoing debates regarding its conformity with Islamic law, suluk remains an interesting subject of study, particularly as described by Syeikh Muhammad Said Bonjol in his book Inilah Jalan Kepada Allah, where he refers to suluk as a “spiritual school.” This research employs a library research method by examining written sources, with the works of Syeikh Muhammad Said Bonjol as the material object and his educational thought as the formal object. The findings indicate that suluk is viewed as a method of character education aimed at purifying the soul, where the spiritual dimension serves as the leader of the physical body in human life.